Indicators for dental appointment scheduling in primary health care: a national cross-sectional study - Melo, Estêvão Azevedo; Probst, Livia Fernandes; Guerra, Luciane Miranda; Tagliaferro, Elaine Pereira da Silva [UNESP]; De-Carli, Alessandro Diogo; Pereira, Antonio Carlos (Springer Nature, 2021)
Background: Integrated dental services within the Health System, particularly at primary health care, are crucial to reverse the current impact of oral diseases, which are among the most prevalent diseases worldwide. However, the use of dental services is determined by complex phenomena related to the individual, the environment and practices in which care is offered. Therefore, factors associated with dental appointments scheduling can affect positively or negatively the use of dental services. The aim of the present study was to evaluate the indicators for dental appointment scheduling in Primary Health Care (PHC). Methods: The present is a cross-sectional analytical study that used data from the external assessment of the third cycle of the National Program for Improving Access and Quality in Primary Care (PMAQ-AB), carried out between 2017 and 2018, in Brazil. The final sample consisted of 85,231 patients and 22,475 Oral Health teams (OHTs). The outcome variable was the fact that the user sought for a dental appointment at the Primary Health Care Unit. A multilevel analysis was carried out to verify the association between individual variables (related to users) and contextual variables (related to the OHTs) in relation to the outcome. Results: Only 58.1% of the users interviewed at these Primary Health Care Units seek the available dental care. The variables with the greatest effect on the outcome were the patient’s age up to 42 years old (OR = 2.03, 95% CI: 1.96–2.10), at individual level, and ‘oral health teams that assisted no more than a single family health team (FHT)’ (OR = 1.29, 95% CI: 1.23–1.36) at contextual level. Other variables were also associated with the outcome, but with a smaller effect size. Conclusion: In conclusion, users’ age and work process of OHT were indicators for dental appointment scheduling. Our results suggest that when OHT put the National Oral Health Policy guidelines into practice, by assisting only one FHT, the chance for PHC users seeking dental appointments is higher than OHTs that assist more than one FHT. Regarding age, patients aged up to 42 years are more likely to seek an appointment with a dentist.
Keywords: Community dentistry; Dental health services; Public health dentistry; Public health practice; Public health systems research